Management of Mentoring to Improve the Quality of Learning at SMP Negeri 3 Magelang City - Retno Setyaningrum; Rahmat Mulyono; Jumintono (JURNAL MANAJEMEN PENDIDIKAN, 2026)
This study aims to explore and examine the management of mentoring to improve the quality of learning at SMPN 3 Magelang. The method used in this study was a qualitative descriptive method. The focus was on the implementation of mentoring carried out so that it could contribute to improving the quality of learning at SMPN 3 Magelang in 2024. In this study, the author also used interview and documentation techniques to obtain data regarding the implementation of mentoring. Based on the available data, the author attempted to explore and examine the implementation of mentoring at SMPN 3 Magelang. The results of the study showed that supervisors (educational unit mentors) assisted SMPN 3 Magelang in improving the quality of learning through a flow consisting of four stages, namely mentoring planning up to the determination of mentoring methods and strategies, mentoring for the planning of educational unit work programs up to budgeting, mentoring for the implementation of educational unit work programs with periodic feedback, and the preparation of mentoring reports. During the implementation of mentoring, the principles applied were professionalism, planned and strategic approaches, gradual and independent processes, collaboration, asymmetry, equality, and evaluation-based approaches.